2021
DOI: 10.3389/fphar.2020.570867
|View full text |Cite
|
Sign up to set email alerts
|

Saponins in Chinese Herbal Medicine Exerts Protection in Myocardial Ischemia–Reperfusion Injury: Possible Mechanism and Target Analysis

Abstract: Myocardial ischemia is a high-risk disease among middle-aged and senior individuals. After thrombolytic therapy, heart tissue can potentially suffer further damage, which is called myocardial ischemia-reperfusion injury (MIRI). At present, the treatment methods and drugs for MIRI are scarce and cannot meet the current clinical needs. The mechanism of MIRI involves the interaction of multiple factors, and the current research hotspots mainly include oxidative stress, inflammation, calcium overload, energy metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 125 publications
(73 reference statements)
0
32
0
1
Order By: Relevance
“…In recent years, many studies have shown that the saponins extracted from herbal are great protective of myocardial I/R injury in vivo and in vitro . The mechanisms are diverse and mainly involve regulating energy metabolism and calcium homeostasis, and inhibiting oxidative stress and inflammation ( 172 ).…”
Section: Cardioprotective Phytochemicals Attenuating Myocardial I/r I...mentioning
confidence: 99%
“…In recent years, many studies have shown that the saponins extracted from herbal are great protective of myocardial I/R injury in vivo and in vitro . The mechanisms are diverse and mainly involve regulating energy metabolism and calcium homeostasis, and inhibiting oxidative stress and inflammation ( 172 ).…”
Section: Cardioprotective Phytochemicals Attenuating Myocardial I/r I...mentioning
confidence: 99%
“…Ginseng, a perennial plant belonging to the Araliaceae family (Panax genus), has been extensively studied for its antioxidant defense mechanism with potential protection against MIRI [37][38][39]. Ginseng is particularly used in Asian countries for thousands of years to maintain body homeostasis and energy enhancement [37,40,41].…”
Section: Ginsenosidementioning
confidence: 99%
“…Lack of clinical studies that involve ginsenosides are associated with their low bioavailability (poor water solubility and biomembrane permeability, instability in gastrointestinal tract, and high metabolic rate in the body [27]. Previous reviews on the effects of ginsenosides in MIRI were broad, discussing various types and aspects of ginsenoside in general [11,28]. Therefore, in the present review, we aimed to focus on the mechanism of major components of ginsenosides (Rb), emphasizing the molecular-signaling pathway responsible for the cardioprotective effects against MIRI specifically in ex vivo, in vivo, and in vitro models.…”
Section: Introductionmentioning
confidence: 99%
“…В ряде исследований было установлено также, что некоторые сапонины (гинзенозиды, арджунолевая кислота, астрагалозид IV), алкалоиды (сальсолинол, хигенамин, лигустразин), полисахариды (Ophiopogon, Lycium barbarum, Astragalus), вещества, используемые в традиционной Китайской медицине, могут влиять на процессы ремоделирования миокарда (гипертрофия, фиброз, апоптоз, ангиогенез), уменьшать степень окислительного стресса, митохондриальной дисфункции, хронического системного воспаления [111][112][113][114][115][116].…”
Section: фитотерапевтические подходыunclassified